Cognitive function in late‐stage HFpEF patients with tricuspid regurgitation undergoing transcatheter tricuspid valve intervention. Issue 7 (19th October 2022) - Gerçek, Muhammed; Irimie, Anca A.; Gerçek, Mustafa; Fox, Henrik; Fortmeier, Vera; Rudolph, Tanja K.; Rudolph, Volker; Friedrichs, Kai P.
Abstract: Objectives: This study evaluates the impact of transcatheter tricuspid valve interventions (TTVI) on cognitive function (CF), quality of life (QOL), and exercise capacity in late‐stage heart failure with preserved ejection fraction (HFpEF) and relevant tricuspid regurgitation (TR). Background: Reduced cardiac output (CO) critically affects CF. Severe TR aggravates CO reduction in HFpEF, while TTVI has been demonstrated to re‐establish CO to a significant extent. The effect of TTVI on CF of HFpEF patients has so far not been investigated. Methods: Assessment of CF was performed using the standardized Montreal Cognitive Assessment test in 34 symptomatic HFpEF patients with at least severe TR before and 3 months after TTVI alongside echocardiographic examinations and assessment of exercise capacity and QOL. Results: Median age of the patients was 81.0 [78.8; 83.0] years and 50.0% were female. CF was impaired in 67.6% of the patients. TR ≤ moderate was achieved in 94.1% of the cases. Overall CF improved significantly (from 20.6 ± 3.9 to 23.0 ± 4.4; p  = 0.001). Particularly, significant improvements were identified in the executive function ( p  < 0.001) and memory ( p  = 0.008). In addition, linear regression analysis demonstrated a significant collinearity of improvement between executive function as well as memory and increased CO ( ρ  = 0.695; p  < 0.001 and ρ  = 0.628; p  < 0.001, respectively). The walked distance and QOL also improved significantly 3 months after TTVI. Conclusion: Cognitive impairment is highly prevalent in HFpEF patients with severe TR. TTVI results in an improved CF, especially with regard to executive function and memory. These improvements also correlate with more efficient hemodynamics reflected by increased CO. Prespective: What is known : Reduced cardiac output (CO) critically affects cognitive function (CF). Severe tricuspid regurgitation (TR) aggravates CO reduction in patients with heart failure with persevered ejection fraction (HFpEF) for which therapeutics option were so far limited, while transcatheter tricuspid (TTVI) valve intervention has been demonstrated to re‐establish CO to a significant extent. What is new : TTVI results in improved CF in HFpEF patients, especially concerning executive function and memory and these improvements are closely correlating with more effective hemodynamics reflected by increased CO, exercise capacity and quality of life. What is next : The presence of HFpEF should further entail the assessment of TR as TTVI is emerging as a therapeutic tool to treat late‐stage complications in HFpEF patients with TR.